1970
DOI: 10.1111/j.1744-7348.1970.tb06426.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantities and qualities of leaf protein concentrates from wild species and crop species grown under controlled conditions

Abstract: The amount of protein produced per m2 by plants cultivated in soil in a greenhouse at three levels of fertilizer application, for c. 10 weeks, was estimated by Kjeldahl analysis of the TCA-insoluble fraction of freeze-dried material. The quantity of protein extractable for production of leaf protein concentrates was determined by Kjeldahl analysis of non-dried but frozen material after disintegration with a meat mincer and an Ultra-Turrax homogenizer, hydraulic pressing and filtration, and protein precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

1974
1974
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…These data are in agreement with results by Wall et al (1975), Sozinov (1985) and Ganesh and Grieve (1990). McDonald (1982) reported that the content of NPN in red clover leaves and stems was 13É8 and 37É4% of total N, respectively, while Lexander et al (1970) found that the NPN was between 3É7 and 32É5% of the protein N over a wide range of forage plants. They concluded that nitrogenous fertilisers increased the NPN content of both grasses and legumes.…”
Section: Discussionmentioning
confidence: 98%
“…These data are in agreement with results by Wall et al (1975), Sozinov (1985) and Ganesh and Grieve (1990). McDonald (1982) reported that the content of NPN in red clover leaves and stems was 13É8 and 37É4% of total N, respectively, while Lexander et al (1970) found that the NPN was between 3É7 and 32É5% of the protein N over a wide range of forage plants. They concluded that nitrogenous fertilisers increased the NPN content of both grasses and legumes.…”
Section: Discussionmentioning
confidence: 98%
“…1998). N and respiration may be related because most of N is in protein (Lexander et al . 1970), which requires maintenance respiration for repair and replacement (Ryan 1991).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis proposed to explain differences in maintenance respiration is that tissue N varies within and between tissues (Ryan 1991). In this model, N is used as an easily measured surrogate for protein concentration because most of the nitrogen in plant cells is associated with protein (Lexander et al . 1970).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…amounts of extractable protein (Lexander et al 1970 Pedersen and Wang (197 l), have been detected inAmaranthus foliage at high levels (Cheeke, unpubl. observ.).…”
mentioning
confidence: 99%